Kontribusi Manajemen Mutu, Budaya Organisasi, dan Lingkungan Kerja pada Kinerja Pegawai (Studi pada Kantor Satpol PP dan Wilayatul Hisbah Kabupaten Bireuen) - Sufiani, Sufiani; Ibrahim, Ibrahim; Danil, Mahyu; Hadi, Abdul (Singkite Journal, 2025)
This study aims to empirically test the contribution of quality management, organizational culture, and the work environment to employee performance. The study took the form of a survey at the Civil Service Police Unit and Wilayatul Hisbah (Satpol PP and WH) Office in Bireuen Regency. 123 employees were used as respondents, using an associative method. The analysis used a path model. The study results revealed: (1) a positive contribution of quality management to employee performance of 43.18%, while organizational culture contributed 41.18%, and the work environment 60.29%. (2) simultaneously, quality management, organizational culture, and the work environment had a significant impact on employee performance of 52,2%. (3) a causal relationship exists between the variables of quality management, organizational culture, and the work environment, with a moderate category.